Translation of Auxiliary Verbs in Novel the Fault in Our Stars - Maureen Vanessa Yoel; Agung Prasetyo Wibowo (ITScience (Information Technology and Science), 2023)
This study intends to: (i) analyze the forms of auxiliary verbs and their translation found in the data source, (ii) analyze the translation strategies used in the translation process from the source language and target language. This research study focuses on English auxiliary verbs and their translations into Indonesian found in the novel entitled “The Fault in Our Stars” and the translation strategies in the translation process. In analyzing the data, the analysis uses the translation strategies proposed by (Chesterman, 2016). The method that the researcher employs is namely qualitative method, while the approach is descriptive qualitative. The data taken is purposeful sampling. The data taken for each auxiliary verbs are 50 data. This research shows that most of the English auxiliary verbs are not translated in Indonesian because there is no fixed equivalent for auxiliary verbs in Indonesian. There are only four strategies out of thirty strategies proposed by Chesterman are used. The strategies are literal (7 data), transposition (28 data), unit shift (12 data), and compression (28 data). Moreover, the dominant strategy used are transposition and compression, for each of them is 28 data. Thus, it can be implied that only 2 of 30 translation strategies that mostly used in translating auxiliary verbs.